2006
DOI: 10.1371/journal.pgen.0020196
|View full text |Cite
|
Sign up to set email alerts
|

Functional Identification of Api5 as a Suppressor of E2F-Dependent Apoptosis In Vivo

Abstract: Retinoblastoma protein and E2-promoter binding factor (E2F) family members are important regulators of G1-S phase progression. Deregulated E2F also sensitizes cells to apoptosis, but this aspect of E2F function is poorly understood. Studies of E2F-induced apoptosis have mostly been carried out in tissue culture cells, and the analysis of the factors that are important for this process has been restricted to the testing of a few candidate genes. Using Drosophila as a model system, we have generated tools that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
119
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(143 citation statements)
references
References 57 publications
15
119
0
3
Order By: Relevance
“…Non-small cell lung cancer patients whose cancers express API5 have a poorer prognosis than patients with non-API5-expressing cancers, and overexpression of API5 promotes the invasion and inhibits apoptosis in cervical cancer cells (15,17,20). It has been suggested that API5 suppresses E2F1 transcription factor-induced apoptosis (21). A recent study also suggested that API5 is phosphorylated by PIM2 kinase and inhibits apoptosis in hepatocellular carcinoma cells through NF-B (nuclear factor-B) (22).…”
Section: Apoptosis Inhibitor 5 (Api5) Is An Anti-apoptotic Protein Thmentioning
confidence: 99%
“…Non-small cell lung cancer patients whose cancers express API5 have a poorer prognosis than patients with non-API5-expressing cancers, and overexpression of API5 promotes the invasion and inhibits apoptosis in cervical cancer cells (15,17,20). It has been suggested that API5 suppresses E2F1 transcription factor-induced apoptosis (21). A recent study also suggested that API5 is phosphorylated by PIM2 kinase and inhibits apoptosis in hepatocellular carcinoma cells through NF-B (nuclear factor-B) (22).…”
Section: Apoptosis Inhibitor 5 (Api5) Is An Anti-apoptotic Protein Thmentioning
confidence: 99%
“…Dyson and colleagues identified the anti-apoptotic protein Api5 in a screen for suppressors of E2F-mediated apoptosis in Drosophila [63]. Api5 specifically affects E2F-driven apoptosis both in flies and human cells, having no effect on other inducers of cell death.…”
Section: Regulation Of Pro-apoptotic Functions Of E2f By Interacting mentioning
confidence: 99%
“…First, global Drosophila genetic screening identified API-5 as a suppressor of apoptosis mediated by E2 promoter-binding factors (E2F) in multiple cell types and developmental contexts (5). This genetic interaction was confirmed in human cancer cells in vitro and appears to be mediated by API-5 binding and inactivation of acinus, a protein necessary for apoptotic DNA fragmentation (5,6). Second, API-5 protected tumor cells against the stress generated by suboptimal growth conditions or death-triggering chemicals, as demonstrated by Rigou et al, who found a marked increase of etoposide-and camptotecininduced apoptosis in various types of cancer cells caused by a depletion in the level of API-5 (6).…”
Section: Introductionmentioning
confidence: 78%
“…API-5 was originally identified based upon its marked anti-apoptotic action, demonstrated in mouse BALB/c3T3 fibroblasts, human cervical carcinoma CUMC-6 cells and immortalized primary liver THLE-3 cells, where ectopic API-5 expression significantly enhanced the cell survival following serum withdrawal or UV irradiation (1)(2)(3)(4). Similarly, a decrease in API-5 levels sensitized human squamous cell carcinoma (JHU-029), colon cancer (HCT116), cervical cancer (HeLa), lung adenocarcinoma (A549), acute lymphoblastic leukemia (Molt-4), endothelial (HUVEC) and osteosarcoma (U20S) cells to a number of forms of apoptosis, demonstrating the pro-survival signaling of API-5 in several experimental tumor cell systems in vitro (4)(5)(6).…”
Section: Introductionmentioning
confidence: 98%